Integration of the Pancasila Student Profile Strengthening Project with Design Thinking in the Merdeka Curriculum: Stimulating Students' Creative Thinking Skills - Herianingtyas, Nur Luthfi Rizqa; Marini, Arita; Zakiah, Linda; Chen, Yinghuei (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
AbstractIn the context of the 21st-century society, creative thinking skills stand out as pivotal competencies. Nevertheless, many countries, Indonesia included, grapple with a crisis in nurturing these skills among students. This research addresses this challenge by integrating the Pancasila Student Profile Strengthening Project with Design Thinking (DT) methodologies. Fifty-four fifth-grade students from a Madrasah Ibtidaiyah in Pacitan, East Java, Indonesia, participated in this study, which employed a mixed-methods approach combining qualitative and quantitative techniques. Qualitative data were gathered through interviews and observations, while quantitative data were collected through tests assessing creative thinking skills, specifically Fluency, Flexibility, Originality, and Elaboration. Guided by the five stages of DT—Empathise, Define, Ideate, Prototype, and Test—the integration of P5 with DT facilitated the development of students' original ideas and the creation of problem-solving products tailored to meet community needs. The findings underscore the significant efficacy of this integrated approach in enhancing students' creative thinking skills, particularly evident in marked improvements in originality and elaboration. This study contributes valuable insights for elevating critical thinking abilities among elementary school and Madrasah Ibtidaiyah students through DT methodologies.AbstrakDalam konteks masyarakat abad ke-21, keterampilan berpikir kreatif menonjol sebagai kompetensi yang sangat penting. Namun, banyak negara, termasuk Indonesia, menghadapi krisis dalam mengembangkan keterampilan ini di kalangan siswa. Penelitian ini mengatasi tantangan tersebut dengan mengintegrasikan Proyek Penguatan Profil Pelajar Pancasila dengan metodologi Design Thinking (DT). Penelitian ini melibatkan lima puluh empat siswa kelas lima dari Madrasah Ibtidaiyah di Pacitan, Jawa Timur, Indonesia, dengan menggunakan pendekatan campuran yang menggabungkan teknik kualitatif dan kuantitatif. Data kualitatif diperoleh melalui wawancara dan observasi, sedangkan data kuantitatif dikumpulkan melalui tes yang menilai keterampilan berpikir kreatif, khususnya Kelancaran, Fleksibilitas, Orisinalitas, dan Elaborasi. Dipandu oleh lima tahap DT—Empati, Definisi, Ideasi, Prototipe, dan Uji—integrasi P5 dengan DT memfasilitasi pengembangan ide orisinal siswa dan penciptaan produk pemecahan masalah yang disesuaikan untuk memenuhi kebutuhan masyarakat. Temuan ini menegaskan efektivitas signifikan dari pendekatan terintegrasi ini dalam meningkatkan keterampilan berpikir kreatif siswa, terutama terlihat dalam peningkatan yang signifikan dalam orisinalitas dan elaborasi. Studi ini memberikan wawasan berharga untuk meningkatkan kemampuan berpikir kritis di kalangan siswa sekolah dasar dan Madrasah Ibtidaiyah melalui metodologi DT.